Analysis of Changes in The Erosion Level and Sedimentation in The Tempuran Reservoir Catchment Area of Blora Year 2017-2021 - Wijaya, Arwan Putra; Rosyiidah, Rofi’ Ronaa; Bashit, Nurhadi (Universitas Negeri Semarang, 2024)
Tempuran Reservoir is one of the existing water supply reservoirs in the Jratun Seluna River Basin located in Blora Regency. This reservoir has an important role to store water in the rainy season, provide raw water, and irrigate around 420 ha of surrounding land, so it is necessary to maintain its management so that it can continue to function optimally. However, sedimentation is often the main problem for the reservoir, which occurs as a result of the erosion process in the Tempuran Reservoir Catchment Area which then settles to the bottom of the reservoir. In addition, climatic conditions are thought to be a factor that greatly influences erosion. This is exacerbated by the fact that Blora Regency is an area that often experiences drought due to low rainfall. Therefore, this study aims to determine the development of erosion rates and the level of erosion hazard in the Tempuran Reservoir catchment area in 2017-2021, and to predict the sediment yield flowing into Tempuran Reservoir in 2017-2021. The method used to predict erosion results is the Universal Soil Loss Equation (USLE) and utilizes the Sediment Delivery Ratio (SDR) to predict sediment yield entering the reservoir. The results showed a decrease in the erosion rate of -1773,357 tons/ha/year in 2019 and continued to decrease by -66,694 tons/ha/year in 2021. The most influential factor in reducing the erosion rate in the Tempuran Reservoir catchment area is the rain erosivity factor. Meanwhile, sedimentation carried to Tempuran Reservoir in 2019 decreased by -117,344 tons/ha/year and in 2021 there was also a decrease of -4,413 tons/ha/year.